The Relationship of Serum Zinc Levels and Clinicopathological Characteristics in Individuals with Lung Cancer - Haryati, Haryati; Eko Prasetyo, Nugroho; R. Simarmata, Eviriana; Parhusip, Mual Bobby Enrico; Arganita, Fidya Rahmadhany; Humaira, Adhwa (Indonesian Society of Respirology (ISR), 2024)
Background: Lung cancer is one of the main contributors to malignancy and leads to the patient's death. The immune system, genetics, and inflammation affect lung cancer progression. Zinc (Zn) is an essential mineral; a Zn deficiency increases the tumor suppressor's expression, damaging deoxyribonucleic acid (DNA) repair ability in tumor growth. The study focused on establishing a relationship between serum Zn levels and lung cancer patients' clinicopathologic characteristics. Method: Thirty-five patients diagnosed with lung cancer were part of the study. The study collected clinicopathological data and serum Zn levels at the initial diagnosis. Serum Zn insufficiency is characterized by a below 80 μg/dL serum Zn level. Results: The median Zn level in our study was 65 μg/dL (range=56.5-73 μg/dL). Serum Zn deficiency was observed in 91.4% of patients, particularly those who had a smoking history, advanced stage, or had hypoalbuminemia. The low-level group exhibited significantly lower albumin concentrations (3.06 g/dL vs. 3.66 g/dL; P=0.024) than the normal group. Conclusion: Most patients with lung cancer at initial diagnosis had a deficiency in Serum Zn, which was associated with hypoalbuminemia.